1 answer:
Answer and Step-by-step explanation:
The independent variable is m, and the dependent variable is h.
This is because you can plug in any value for m, making m NOT have to depend on any other value to become m.
With h, it needs the result of m and its other values to become the result of h. H relies/depends on the values in the equation to become a value.
<em><u>#teamtrees #PAW (Plant And Water)</u></em>
You might be interested in
Answer: ![A^{-1}=\left[\begin{array}{cc}\frac{3}{2}&-\frac{1}{2}\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=A%5E%7B-1%7D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B3%7D%7B2%7D%26-%5Cfrac%7B1%7D%7B2%7D%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
<u>Step-by-step explanation:</u>
![\left[\begin{array}{cc}2&1\\4&3\end{array}\right]=\left[\begin{array}{cc}1&0\\0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D2%261%5C%5C4%263%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D)
![\dfrac{1}{2}Row\ 1\rightarrow\left[\begin{array}{cc}1&\frac{1}{2}\\4&3\end{array}\right]=\left[\begin{array}{cc}\frac{1}{2}&0\\0&1\end{array}\right]](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7DRow%5C%201%5Crightarrow%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%26%5Cfrac%7B1%7D%7B2%7D%5C%5C4%263%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B1%7D%7B2%7D%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D)
![Row\ 2 -4 \ Row\ 1\rightarrow \left[\begin{array}{cc}1&\frac{1}{2}\\0&1\end{array}\right]=\left[\begin{array}{cc}\frac{1}{2}&0\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=Row%5C%202%20-4%20%5C%20Row%5C%201%5Crightarrow%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%26%5Cfrac%7B1%7D%7B2%7D%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B1%7D%7B2%7D%260%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
![Row\ 1-\dfrac{1}{2}\ Row\ 2 \rightarrow \left[\begin{array}{cc}1&0\\0&1\end{array}\right]=\left[\begin{array}{cc}\frac{3}{2}&-\frac{1}{2}\\-2&1\end{array}\right]](https://tex.z-dn.net/?f=Row%5C%201-%5Cdfrac%7B1%7D%7B2%7D%5C%20Row%5C%202%20%5Crightarrow%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D1%260%5C%5C0%261%5Cend%7Barray%7D%5Cright%5D%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D%5Cfrac%7B3%7D%7B2%7D%26-%5Cfrac%7B1%7D%7B2%7D%5C%5C-2%261%5Cend%7Barray%7D%5Cright%5D)
Reflection across the y-axis, one unit down, one unit to the right.
Hope It Helps!
Answer:i dont think so
Step-by-step explanation:
Given:
The equation is
![\left(z+\dfrac{6}{7}\right)+\dfrac{2}{14}=-1](https://tex.z-dn.net/?f=%5Cleft%28z%2B%5Cdfrac%7B6%7D%7B7%7D%5Cright%29%2B%5Cdfrac%7B2%7D%7B14%7D%3D-1)
To find:
The solution of the given equation.
Solution:
We have,
![\left(z+\dfrac{6}{7}\right)+\dfrac{2}{14}=-1](https://tex.z-dn.net/?f=%5Cleft%28z%2B%5Cdfrac%7B6%7D%7B7%7D%5Cright%29%2B%5Cdfrac%7B2%7D%7B14%7D%3D-1)
It can be written as
![\left(z+\dfrac{6}{7}\right)+\dfrac{1}{7}=-1](https://tex.z-dn.net/?f=%5Cleft%28z%2B%5Cdfrac%7B6%7D%7B7%7D%5Cright%29%2B%5Cdfrac%7B1%7D%7B7%7D%3D-1)
![\left(z+\dfrac{6}{7}\right)=-1-\dfrac{1}{7}](https://tex.z-dn.net/?f=%5Cleft%28z%2B%5Cdfrac%7B6%7D%7B7%7D%5Cright%29%3D-1-%5Cdfrac%7B1%7D%7B7%7D)
Multiply both sides by 7.
![7z+6=-7-1](https://tex.z-dn.net/?f=7z%2B6%3D-7-1)
![7z+6=-8](https://tex.z-dn.net/?f=7z%2B6%3D-8)
![7z=-8-6](https://tex.z-dn.net/?f=7z%3D-8-6)
![7z=-14](https://tex.z-dn.net/?f=7z%3D-14)
Divide both sides by 7.
![z=\dfrac{-14}{7}](https://tex.z-dn.net/?f=z%3D%5Cdfrac%7B-14%7D%7B7%7D)
![z=-2](https://tex.z-dn.net/?f=z%3D-2)
Therefore, the value of z is -2.
You have to expand the expression so that it becomes
3m+3n